The association between type 1 diabetes mellitus and the risk of immunoglobulin A nephropathy: a Mendelian randomization study - Zhang, Chun-Hua; Shen, Yang; Zhao, Su-Mei (Frontiers in Medicine, 2024)
Objective: To investigate the potential causal relationship between Type 1 Diabetes Mellitus (T1DM) and IgA Nephropathy (IgAN) to deepen understanding of the association between these two conditions and to provide a scientific basis for future preventive and therapeutic strategies. Methods: This study employed Mendelian Randomization (MR) analysis, using single nucleotide polymorphisms (SNPs) derived from genome-wide association studies (GWAS) as genetic instrumental variables (IVs), to assess the association between T1DM and IgAN. The analytical approaches included univariable and multivariable MR, along with sensitivity analyses such as Mendelian Randomization-Egger (MR-Egger) and Mendelian Randomization Pleiotropy RESidual Sum and Outlier (MR-PRESSO), to evaluate the impact of heterogeneity and pleiotropy. Results: Univariable MR analysis using the IVW method revealed an odds ratio (OR) of 1.39 (95% confidence interval (CI): 1.10–1.74) for the association between T1DM and IgAN. Adjusted results from multivariable MR analysis indicated a significant relationship between T1DM and increased risk of IgAN; for example, after adjusting for triglycerides (TG), the OR was 1.534 (CI: 1.213–1.543). After adjustment for HOMA-IR, the OR was 1.303 (CI: 1.149–1.198). Sensitivity analyses, including MR-Egger regression intercept testing (P=0.476), suggested no pleiotropy, and MR-PRESSO did not detect any influence from outlier SNPs. Conclusion: The findings suggest that T1DM is a factor in increasing the risk of IgAN, enhancing our understanding of the potential relationship between T1DM and IgAN and providing possible biological pathways for future disease prevention and intervention.